2005
DOI: 10.1021/jo050091o
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Multioxidants in the pH Dependence of the Reactivity of Ferrate(VI)

Abstract: Alcohol oxidation by ferrate (FeO(4)(2)(-)) in water is investigated from B3LYP density functional theory calculations in the framework of polarizable continuum model. The oxidizing power of three species, nonprotonated, monoprotonated, and diprotonated ferrates, was evaluated. The LUMO energy levels of nonprotonated and monoprotonated ferrates are greatly reduced by solvent effects, and as a result the oxidizing power of these two species is increased enough to effectively mediate a hydrogen-atom abstraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…The activation energy for the C-O bond formation was computed to be 44.4 kJ mol À1 relative to the dissociation limit. The activation barrier is 26.4 kJ mol À1 lower than that for the C-H bond cleavage of methanol by this oxidant, 24 indicating that cyanide is readily converted into cyanate by ferrate in water solution. The produced intermediate 2m lies 104.9 kJ mol À1 below the dissociation limit and has a spin density of 1.0 on the nitrogen atom of the cyanide moiety, which indicates the reduction of the iron atom from charge VI to V. The activation energy of 38.1 kJ mol À1 for TS(2m !…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The activation energy for the C-O bond formation was computed to be 44.4 kJ mol À1 relative to the dissociation limit. The activation barrier is 26.4 kJ mol À1 lower than that for the C-H bond cleavage of methanol by this oxidant, 24 indicating that cyanide is readily converted into cyanate by ferrate in water solution. The produced intermediate 2m lies 104.9 kJ mol À1 below the dissociation limit and has a spin density of 1.0 on the nitrogen atom of the cyanide moiety, which indicates the reduction of the iron atom from charge VI to V. The activation energy of 38.1 kJ mol À1 for TS(2m !…”
Section: Resultsmentioning
confidence: 91%
“…From density functional theory (DFT) calculations, we have investigated the mechanism and energetics of alcohol oxidation 23,24 and alkane hydroxylation 25 by ferrate. These reactions are likely to be initiated by an H-atom abstraction from a C-H or O-H bond.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 (dashed lines). Moreover, density functional theory (DFT) calculations have shown that the protonated form of Fe(VI) has a larger spin density on the oxo ligands than the unprotonated form of Fe(VI), which increases the oxidation ability of protonated Fe(VI) [42].…”
Section: Kinetics For the Reaction Of Fe(vi) With Triclosanmentioning
confidence: 99%
“…However the instability of Fe(VI) has limited its use in water treatment applications, but recent development in the production of Fe(VI) in situ using the electrochemical method makes it a promising oxidant for the real application of Fe(VI) in water and wastewater treatment plants (Yu and Licht, 2008;Alsheyab et al, 2009;Macova et al, 2009). As the oxidant of iron series, Fenton reactions compose reactions of peroxides with iron ions to form active oxygen species at the low pH of 2.8e3.0 that limit their widespread usage (Pignatello et al, 2006) 2-are the predominant species with the oxidizing power of these oxidants increasing in the order nonprotonated ferrate < monoprotonated ferrate < diprotonated ferrate (Kamachi et al, 2005). These pH-dependent variations of Fe(VI) reaction with organic contaminants could be explained by considering species-specific reactions between Fe(VI) species and acid-base species of an ionizable substrates (Lee et al, 2005a;Sharma et al, 2006).…”
Section: Introductionmentioning
confidence: 99%